Study of domestic waste management in flat area / Mohammad Syahmi Mohd Sabri - Mohd Sabri, Mohammad Syahmi (Faculty Architecture, Planninng and Surveying, 2015)
Nowadays, generation of municipal solid wastes (MSW) in Malaysia has increased more than 91%. Municipal solid waste management in Malaysia can be considered relatively poor and disorganised .Many urban areas in Malaysia are experiencing waste management problems due to the enhancement of urbanization and industrialization. These are further escalated by urban growth, changing consumption habits as well as social lifestyles. This new growth has been accompanied with an ever increasing rural-urban migration which culminates in the proliferation of squatter areas due to the scarcity of land and resources. Domestic waste issue has been quite critical issue in many countries although it’s already 21st century. Not much country can really overcome or handle this problem even many technique or ways has been implemented. The increase of waste disposal has given rise to collection and disposal problems which could pose as a potential environmental pollution and health risk to the general public through disease transmission and effecting their daily activities. Thus, this dissertation true intention is to know the main reason why the residential area especially flat area, mostly, has the lowest level of cleanliness when it comes to bins or garbage and also to know what is the best waste management system that suitable to keep practising. Taking place in Malaysia, the area of case study of this dissertation is in flat area in Selangor. Most of the occupant who live in that particular area agree that the system need to be improve as well as the rule.